HM+ and HM+‑He (M = Group 2 metal): chemical or physical interactions? - Harris, Joe P.; Dodson, Hannah; Breckenridge, W.H.; Wright, Timothy G. (American Institute of Physics, 2014)
We investigate the HM+–He complexes (M = Group 2 metal) using quantum chemistry. Equilibrium geometries are linear for M = Be and Mg, and bent for M = Ca–Ra; the explanation for this lies in the differing nature of the highest occupied molecular orbitals in the two sets of complexes. The difference primarily occurs as a result of the formation of the H–M+ bond, and so the HM+ diatomics are also studied as part of the present work. The position of the He atom in the complexes is largely determined by the form of the electron density. HM+. . . He binding energies are obtained and are surprisingly high for a helium complex. The HBe+. . . He value is almost 3000 cm−1, which is high enough to suspect contributions from chemical bonding. This is explored by examining the natural orbital density and by population analyses.